2017
DOI: 10.2147/ott.s127872
|View full text |Cite
|
Sign up to set email alerts
|

miR-762 can negatively regulate menin in ovarian cancer

Abstract: Ovarian cancer accounts for the major part of the mortality attributable to female reproductive system malignant tumors worldwide. Recently, the incidence of ovarian cancer has been increasing annually, and there remains a lack of suitable treatment methods that can significantly improve the 5-year survival rates of patients. Therefore, it is necessary to identify more effective treatments for ovarian cancer. It is established that microRNAs (miRNAs) have important roles in the diagnosis and treatment of ovari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 22 publications
(26 reference statements)
0
45
0
1
Order By: Relevance
“…MiR-762 has been reported to serve as oncogene in breast cancer and ovarian cancer 23,24 . To investigate whether miR-762 plays the similar roles in UCB, we first measured the level of miR-762 in UCB cells and 31 pairs of patient tissues.…”
Section: Mir-762 Is Overexpressed In Ucb Cells and Tissues And Facilmentioning
confidence: 99%
“…MiR-762 has been reported to serve as oncogene in breast cancer and ovarian cancer 23,24 . To investigate whether miR-762 plays the similar roles in UCB, we first measured the level of miR-762 in UCB cells and 31 pairs of patient tissues.…”
Section: Mir-762 Is Overexpressed In Ucb Cells and Tissues And Facilmentioning
confidence: 99%
“…miR-762 is upregulated in radiation-induced tumors in mice and may affect the pathways involved in apoptosis in this context 15 . Previous studies reported abnormal miRNA expression in numerous cancers, and miR-762 overexpression has been reported in breast cancer and ovarian cancer, where it promoted cancer cell growth and metastasis 16,17 . A previous study also demonstrated an association between miR-762 expression and oral carcinogenesis 18 .…”
Section: Discussionmentioning
confidence: 99%
“…In the future, further analysis of the regulation of circulating miR-762 on cancer promotion and progression in CRC patients will be advanced elucidated. Hou et al (2017) reported that miR-762 can downregulate the expression of a tumor suppressor protein menin through a binding site in its 3'-UTR and consequently upregulate the Wnt cell signaling pathway to promote the development of ovarian cancer 17 . Our present study rst revealed that circulating miR-762 expression may be useful as a biomarker for diagnosing CRC and higher serum miR-762 expressioncaused distant metastasis of patients with CRC.…”
Section: Discussionmentioning
confidence: 99%
“…miR-762 is upregulated in radiation-induced tumors in mice and may affect the pathways involved in apoptosis in this context 15 . Several studies reported abnormal miRNA expression in numerous cancers, and miR-762 overexpression has been reported in breast cancer and ovarian cancer, where it promoted cancer cell growth and metastasis 16,17 . A previous study also demonstrated an association between miR-762 expression and oral carcinogenesis 18 To explore the molecular mechanisms by which miR-762 enhances CRC cell growth and invasion, Wnt/b-catenin was identified as a direct target of miR-762 in CRC cells.…”
Section: Discussionmentioning
confidence: 99%